Women's glass ceiling beliefs predict work engagement and burnout. Issue 9 (9th October 2017) - Balasubramanian, Senthil Arasu; Lathabhavan, Remya
Abstract : Purpose: The purpose of this paper is to examine the relationship between glass ceiling beliefs, work engagement, and burnout. Design/methodology/approach: A research model was developed based on the constructs from the Career Path Survey (CPS) and a literature review of research related to work engagement and burnout. Data from a cross-sectional study of 467 female employees from banks in India were collated and empirically tested, using structural equation modeling. Findings: Denial and resilience were positively related to work engagement and negatively to burnout. Resignation and acceptance had a positive relationship with burnout and a negative relationship with work engagement. Research limitations/implications: Further longitudinal studies focusing on different occupational sectors and career aspects can be considered for a more accurate and generalized insight into this concept. Practical implications: Glass ceiling survey can be considered as an input for human resource functions for effectiveness of the organization. Originality/value: This paper is the first to analyze the connection between the beliefs that women have about the glass ceiling and burnout and its components.